Using Co-Solvent Approach to Improve the Performance of Lipase from Thermomyces lanuginosus in Preparation of 5'-O-Palmitoyl-6-azauridine - Bi1, Yanhong; Wang1, Zhaoyu; Nie1, Linghong; Li1, Xiangqian (Asian Journal of Chemistry, 2013)
Organic co-solvents can improve the catalytic power, activity and stability of the enzyme. In this paper, regioselective transesterification of 6-azauridine with vinyl palmitate using immobilized lipase from Thermomyces lanuginosus in the co-solvent system was described. The optimum conditions were screened out. The optimal volumetric ratio of the co-solvent mixture, molar ratio of 6-azauridine to vinyl palmitate and reaction temperature were found to be acetone/isooctane (90:10 v/v), 1:5 and 50 ºC, under which the reaction rate, substrate conversion and 5'-regioselectivity were 20.6 mM/h, >99.0 and 99.0 %, respectively. Moreover, the thermal stability and operational stability of the enzyme were enhanced expressly by changing the reaction solvent from pure acetone to a mixture of acetone and isooctane.